CERM-3726 - J. Castañer; R.T. Owen (Drugs of the Future, 1982)
Objective Endometriosis is a chronic inflammatory disorder that affects approximately 10% of reproductive-age women and is frequently associated with subfertility. This study evaluated the potential ameliorative effect of lactoferrin on endometriosis-associated subfertility in a rat model. Methods Rats were allocated into four groups: Sham, Sham+Lacto, Endo, and Endo+Lacto. In these group labels, "Endo" denotes endometriosis and "Lacto" denotes lactoferrin. Endometriosis was surgically induced in the Endo and Endo+Lacto groups, whereas rats in the Sham and Sham+Lacto groups underwent abdominal incision without uterine manipulation. Lactoferrin (300 mg/kg/day) was orally administered for 30 days to the Sham+Lacto and Endo+Lacto groups. After treatment, five females from each group were mated with mature males to assess fertility index parameters. Results Endo rats exhibited a significant increase in serum follicle-stimulating hormone (FSH) and a significant decrease in serum luteinizing hormone (LH) compared with Sham controls. In addition, marked histopathological alterations were observed in ovarian and eutopic uterine tissues. Maternal uterine and ovarian weights were significantly reduced in the Endo group, whereas fertility index parameters showed no significant differences among the experimental groups. Neonatal outcomes did not differ significantly between the Endo and Sham groups. In contrast, lactoferrin treatment significantly ameliorated gonadotropin imbalance, alleviated ovarian and eutopic endometrial histopathological alterations, and significantly increased neonatal weight and size in endometriotic rats, whereas neonatal length and pup number were not significantly changed. Conclusion Lactoferrin treatment ameliorated gonadotropin imbalance by improving serum FSH and LH levels, restoring ovarian and uterine tissue architecture, and enhancing fertility index parameters and neonatal outcomes. These findings suggest that lactoferrin may represent a promising non-hormonal approach for mitigating endometriosis-associated subfertility.